Measurement of Thermal Effusivity and Thermal Conductivityat Various Water Content for Two Tropical Wood Species - HOUNGAN, COMLAN ARISTIDE; AWANTO, Christophe; DJOSSOU, Ayihaou Armand; ANJORIN, MALAHIMI; VIANOU, Antoine (My University, 2015)
In present work, two tropical wood species were tested: ebony and mahogany. Thermal effusivity and thermal conductivity of wood species were determined in tangential direction depending on water content, usinghot strip method. Results show that thermal effusivity and thermal conductivity of two woods species increase with water content and moreover, for same water content, thermal effusivity and conductivity of ebony are higher than those of mahogany.A comparison with literature data showsfor same water content, axial thermal conductivity is higher than in other directions and tangential thermal conductivity is slightly lower than the radial thermal conductivity.
Keywords: Tropical wood; thermal effusivity; thermal conductivity; water content; hot strip method.